PERANCANGAN INTERIOR POLITEKNIK STTT BANDUNG PROGRAM STUDI PRODUKSI GARMEN - Desty Istiqomalia; Ratri Wulandari; Arief Hapsoro (Universitas Mercu Buana, 2020)
To face the development of industry 4.0, learning facilities in school or college require a change. Facilities as infrastructure in school have a significant role in creating a way of life and work until the innovation of connectivity and creativity necessary for the Industry 4.0 era. As said by Aeji in Robert (2007) that 'facilities have to be adequate and should be in good condition for schools to function properly.' However, in fact, until now, learning facilities in Indonesia has not been concerns properly. The Indonesian education system is like the 19th century, Teachers are like the 20th century, and students are like 21st century'. (MENDIKBUD, 2014-2015). Therefore, require is needed to compensating technological advances in this era, where all human activity involves digital technology-based Cyber-Physical System (data dan cloud computing). The purpose of design is to design learning facilities with a technological approach to create integrity study space-based on technology industry 4.0. As well as Polytechnic STTT Bandung, the only collage government is under the ministry of industry, become objects of design.